Analysis of Labor Migration in Malaysia using the Cost Benefit Analysis (a case study in Malang Regency) - Rizal, Mohammad; Mustapita, Arini Fitria (Universitas Islam Malang, 2017)
The main purpose of individuals working is to make high rate money, this kind of matter is certainly makes interesting to migrate overseas to places where it has high standard wages, one of ways to take this matter is to be international migrant workers or Indonesian Workers. Economic disparity between countries is one of the most dominant reasons that encourage migration among Indonesians. Malaysia is one of the destination countries of Indonesian workers due to the stigma from the community that the same cultural factors, the cognate language, geography, security and of course the wages received. Malang Regency is one of the largest areas of Indonesian workers who contribute quite a large number of Indonesian workers abroad.This study aims to (1) know the things that are faced by migrant workers from Malaysia during pre-placement, placement and after placement (2) to know what is the cost benefit that will be borne by migrant workers from Malaysia.The results of the study indicate that: (1) There are a lot of Indonesian migrant workers involved in the problem, from the time of departure with less capital, the recruitment agency with the problem or the salary cut is too large, while in the destination country to get employer or less conducive work place and when returning to Indonesia with little money or fraud under the guise of travel, but there is also a successful salary and adequate remittance money. (2) Based on the calculation of Cost Benefit Analysis of 15 ex-migrants as a whole qualifies for priority, because in the Net Present Benefit (NPB) and the Method of Benefit Cost Ratio (BCR) all imply that the results of calculations feasible